Detecting Early Markers of Ventilator-Associated Pneumonia by Analysis of Exhaled Gas. Issue 3 (March 2019) - Kunze-Szikszay, Nils; Walliser, Karoline; Luther, Jakob; Cambiaghi, Barbara; Reupke, Verena; Dullin, Christian; Vautz, Wolfgang; Bremmer, Felix; Telgheder, Ursula; Zscheppank, Cornelia; Quintel, Michael; Perl, Thorsten
Abstract : Objectives: The detection of microbial volatile organic compounds or host response markers in the exhaled gas could give an earlier diagnosis of ventilator-associated pneumonia. Gas chromatography-ion mobility spectrometry enables noninvasive, rapid, and sensitive analysis of exhaled gas. Using a rabbit model of ventilator-associated pneumonia we determined if gas chromatography-ion mobility spectrometry is able to detect 1) ventilator-associated pneumonia specific changes and 2) bacterial species-specific changes in the exhaled gas. Design: Experimental in vivo study. Setting: University research laboratory. Subjects: Female New Zealand White rabbits. Interventions: Animals were anesthetized and mechanically ventilated. To induce changes in the composition of exhaled gas we induced ventilator-associated pneumonia via endobronchial instillation of either Escherichia coli group ( n = 11) or Pseudomonas aeruginosa group ( n = 11) after 2 hours of mechanical ventilation. In a control group ( n = 11) we instilled sterile lysogeny broth endobronchially. Measurements and Main Results: Gas chromatography-ion mobility spectrometry gas analysis, CT scans of the lungs, and blood samples were obtained at four measurement points during the 10 hours of mechanical ventilation. The volatile organic compound patterns in the exhaled gas were compared and correlated with ventilator-associated pneumonia severity. Sixty-seven peak areas showed changes in signal intensity in the serial gas analyses. The signal intensity changes in 10 peak regions differed between the groups. Five peak areas (P_648_36, indole, P_714_278, P_700_549, and P_727_557) showed statistically significant changes of signal intensity. Conclusions: This is the first in vivo study that shows the potential of gas chromatography-ion mobility spectrometry for early detection of ventilator-associated pneumonia specific volatile organic compounds and species differentiation by noninvasive analyses of exhaled gas. Abstract : Supplemental Digital Content is available in the text.